Tin and Mixed Lead–Tin Halide Perovskite Solar Cells: Progress and their Application in Tandem Solar Cells. Issue 27 (13th February 2020) - Gu, Shuai; Lin, Renxing; Han, Qiaolei; Gao, Yuan; Tan, Hairen; Zhu, Jia
Abstract: Metal halide perovskites have recently attracted enormous attention for photovoltaic applications due to their superior optical and electrical properties. Lead (Pb) halide perovskites stand out among this material series, with a power conversion efficiency (PCE) over 25%. According to the Shockley–Queisser (SQ) limit, lead halide perovskites typically exhibit bandgaps that are not within the optimal range for single‐junction solar cells. Partial or complete replacement of lead with tin (Sn) is gaining increasing research interest, due to the promise of further narrowing the bandgaps. This enables ideal solar utilization for single‐junction solar cells as well as the construction of all‐perovskite tandem solar cells. In addition, the usage of Sn provides a path to the fabrication of lead‐free or Pb‐reduced perovskite solar cells (PSCs). Recent progress in addressing the challenges of fabricating efficient Sn halide and mixed lead–tin (Pb–Sn) halide PSCs is summarized herein. Mixed Pb–Sn halide perovskites hold promise not only for higher efficiency and more stable single‐junction solar cells but also for efficient all‐perovskite monolithic tandem solar cells. Abstract : Recent progress of tin and mixed Pb–Sn halide perovskite solar cells is summarized, including an introduction of device structures, fabrication methods, strategies to improve both performance and stability, and an outlook of pure tin‐based halide, mixed Pb–Sn halide, and monolithic all‐perovskite tandem solar cells.